Intermittent high altitude--induced changes in energy metabolism in the rat myocardium and their reversibility - Bass, A; Ostádal, B; Procházka, J; Pelouch, V; Samánek, M; Stejskalová, M (Physiologia Bohemoslovaca, 1989)
Selected enzyme activities of energy metabolism were studied in the myocardium of laboratory rats exposed to intermittent altitude hypoxia (IAH, 4-8 h daily, 5 days a week, in a hypobaric chamber, stepwise up to 7,000 m). No significant differences were found between the right and the left ventricle in the control animals. Glucose-utilizing capacity (HK) and capacity for the synthesis and degradation of lactate (LDH) increased significantly in both ventricles during acclimatization. The other enzyme activities associated with anaerobic glycolysis (TPDH, GPDH) and those linked up in aerobic metabolism (MDH, CS) did not change significantly. On the other hand, the ability to break down fatty acids (HOADH) decreased significantly. All the above changes in the enzyme profile were found after only 24 4-h exposures, in both the hypertrophic right ventricle and the unenlarged left ventricle. When the length of daily exposure was raised from 4 to 8 h, the above changes were not intensified and 45 days after the last exposure to IAH, none of the given activity values differed from those estimated in the corresponding control animals.
Keywords: výšková nemoc; Altitude Sickness; Hypoxia; hypoxie; Myocardium; Male; Rats; 3-Hydroxyacyl CoA Dehydrogenases; inbrední kmeny potkanů; glyceraldehyd-3-fosfátdehydrogenasy; 3-hydroxyacyl-CoA-dehydrogenasy; NADH Dehydrogenase; Animals; Hexokinase; zvířata; mužské pohlaví; hexokinasa; Rats, Inbred Strains; Glyceraldehyde-3-Phosphate Dehydrogenases; myokard; krysa rodu Rattus; L-Lactate Dehydrogenase; energetický metabolismus; citrátsynthasa; L-laktátdehydrogenasa; NADH-dehydrogenasa; Energy Metabolism; Citrate (si)-Synthase